Association Between Depression, Health Beliefs, and Face Mask Use During the COVID-19 Pandemic - Bressington, Daniel Thomas; Cheung, Teris Cheuk Chi; Lam, Simon Ching; Suen, Lorna Kwai Ping; Fong, Tommy Kwan Hin; Ho, Hilda Sze Wing; Xiang, Yu-Tao (Frontiers in Psychiatry, 2020)
The 2019 novel coronavirus (COVID-19) pandemic is associated with increases in psychiatric morbidity, including depression. It is unclear if people with depressive symptoms understand or apply COVID-19 information differently to the general population. Therefore, this study aimed to examine associations between depression, health beliefs, and face mask use during the COVID-19 pandemic among the general population in Hong Kong. This study gathered data from 11,072 Hong Kong adults via an online survey. Respondents self-reported their demographic characteristics, depressive symptoms (PHQ-9), face mask use, and health beliefs about COVID-19. Hierarchical logistic regression was used to identify independent variables associated with depression. The point-prevalence of probable depression was 46.5% (n = 5,150). Respondents reporting higher mask reuse (OR = 1.24, 95%CI 1.17–1.34), wearing masks for self-protection (OR = 1.03 95%CI 1.01–1.06), perceived high susceptibility (OR = 1.15, 95%CI 1.09–1.23), and high severity (OR = 1.33, 95%CI 1.28–1.37) were more likely to report depression. Depression was less likely in those with higher scores for cues to action (OR = 0.82, 95%CI 0.80–0.84), knowledge of COVID-19 (OR = 0.95, 95%CI 0.91–0.99), and self-efficacy to wear mask properly (OR = 0.90 95%CI 0.83–0.98). We identified a high point-prevalence of probable major depression and suicidal ideation during the COVID-19 outbreak in Hong Kong, but this should be viewed with caution due to the convenience sampling method employed. Future studies should recruit a representative probability sample in order to draw more reliable conclusions. The findings highlight that COVID-19 health information may be a protective factor of probable depression and suicidal ideation during the pandemic. Accurate and up-to-date health information should be disseminated to distressed and vulnerable subpopulations, perhaps using digital health technology, and social media platforms to prompt professional help-seeking behavior.